THE POWER BALANCE IN CENTRAL ASIA: THE STRATEGIC PARTNERSHIP OF RUSSIAN FEDERATION WITH REPUBLIC OF KAZAKHSTAN (2010-2014) - Megawati Putri; AnakAgung Banyu Perwita (AEGIS : Journal of International Relations, 2016)
The strategic value of the Central Asia region attracts Russia, United States (U.S.) and China to try to get closer with the region. The abundant energy reserves and strategic location to spread military influence leads Central Asia becoming a strategic arena. Seeing the competition of external interested parties in Central Asia, it increases the awareness of Russian Federation as the major power which has already become a dominant actor on that region since the collapse of Soviet Union; as the big brother of former Soviet Union, Russia feels the stabilization of the region becomes Russian responsibility.  To prevent the spreading of external major powers on the region and to manage the power balance in Central Asia, Russia sets its military strategy to keep its military influence in the region. The main focus of this article is presenting the implementation of Russian military strategies by utilize its strategic partnership with Kazakhstan as the shortcut to succeed the implementation of those military strategies.